Thermal conductive sheet
Patent Information
- Application Number
- JP2023184730
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2018-09-26
- Filing Date
- 2023-10-27
- Publication Date
- 2024-12-19
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing thermally conductive sheets face limitations in enhancing thermal conductivity in the thickness direction, primarily due to the roughening of surfaces during slicing, which decreases adhesion and increases thermal resistance.
The thermally conductive sheet is produced by polishing the sliced surfaces to expose anisotropic fillers, ensuring an arithmetic mean curvature of the peaks is 18000 (1/mm) or less, thereby improving surface smoothness and reducing thermal resistance.
This approach enhances thermal conductivity in the thickness direction while maintaining high adhesion to contacting surfaces, achieving a thermal resistance value of less than 1°C/W and thermal conductivity of 18 W/m K or more.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to a thermally conductive sheet, and more particularly to a thermally conductive sheet that is used by being disposed between a heat generating body and a heat dissipating body, for example. [Background technology]
[0002] In electronic devices such as computers, automobile parts, and mobile phones, heat sinks and other heat dissipators are commonly used to dissipate heat generated from heat-generating elements such as semiconductor elements and mechanical parts. It is known that a thermally conductive sheet is placed between the heat-generating element and the heat dissipator to improve the efficiency of heat transfer to the heat dissipator. Thermally conductive sheets are generally compressed when placed inside electronic devices, and therefore require high flexibility. Therefore, they are constructed by blending a thermally conductive filler into a highly flexible polymer matrix such as rubber or gel. It is also widely known that thermally conductive sheets have anisotropic fillers, such as carbon fibers, oriented in the thickness direction to enhance thermal conductivity in the thickness direction (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 2018-056315 [Patent Document 2] Japanese Patent Application Publication No. 2018-014534 Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, with the increasing functionality of electrical devices, there has been an increasing need for thermally conductive sheets with improved properties, and there is a demand for further increasing the thermal conductivity in the thickness direction. However, as disclosed in Patent Documents 1 and 2, there is a limit to how much the thermal conductivity can be increased by simply orienting the filler in the thickness direction, and further improvements are desired. The present invention has been made in view of the above problems, and an object of the present invention is to provide a thermally conductive sheet that can sufficiently improve thermal conductivity in the thickness direction. [Means for solving the problem]
[0005] As a result of extensive research aimed at solving the above-mentioned problems, the inventors first attempted to increase the contact area between the surface of a thermally conductive sheet containing an anisotropic filler such as carbon fiber and a contact surface such as a heat sink by exposing a portion of the anisotropic filler. However, when producing the thermally conductive sheet, the sheet is sliced into sheets using a blade. However, simply slicing the sheet into sheets not only results in roughening of the surface due to slicing, but also in the exposed cut surfaces of the carbon fibers, etc., on the sliced surface, resulting in a rough sheet surface. There is a concern that a roughened sheet surface will reduce adhesion to the contact surface, resulting in an increase in thermal resistance.
[0006] Therefore, the inventors polished the sliced surface to expose the anisotropic filler from the surface of the sheet, while smoothing the arithmetic mean curve (Spc) of the peaks to a predetermined value or less; specifically, by rounding and smoothing the contact points with the contact surface of a heating element, etc., they succeeded in obtaining a thermally conductive sheet that increases adhesion to the contact surface, reduces thermal resistance, and sufficiently improves thermal conductivity in the thickness direction. That is, the present invention is as follows.
[0007] [1] A thermally conductive sheet containing an anisotropic filler in a polymer matrix, in which the anisotropic filler is exposed on at least one surface, and the arithmetic mean peak curvature (Spc) is 18,000 (1 / mm) or less. [2] The thermally conductive sheet according to [1], wherein the anisotropic filler is oriented in the thickness direction of the thermally conductive sheet. [3] The thermally conductive sheet according to [1] or [2], wherein at least one of the surfaces has an arithmetic mean height (Sa) of 20 μm or less. [4] The thermally conductive sheet according to any one of [1] to [3], wherein the surface (at least one surface) of the thermally conductive sheet has an interface developed area ratio (Sdr) of 70 or less. [5] The thermally conductive sheet according to any one of [1] to [4], wherein the anisotropic thermally conductive filler is at least one of a fibrous filler and a scaly filler. [6] The thermally conductive sheet according to any one of [1] to [5], having a thickness of 0.1 to 5.0 mm. [7] The thermally conductive sheet according to [6], which has a thickness of 0.1 to 0.3 mm. [Effects of the Invention]
[0008] According to the present invention, it is possible to provide a thermally conductive sheet that can sufficiently improve thermal conductivity in the thickness direction. [Brief explanation of the drawings]
[0009] [Figure 1] 1 is a schematic cross-sectional view showing a thermally conductive sheet according to a first embodiment. [Figure 2] FIG. 4 is a schematic cross-sectional view showing a thermally conductive sheet according to a second embodiment. [Figure 3] FIG. 1 is a schematic diagram of a thermal resistance measuring device. DETAILED DESCRIPTION OF THE INVENTION
[0010] Hereinafter, the thermally conductive sheet according to the embodiment of the present invention will be described in detail. [First embodiment] Fig. 1 shows a thermally conductive sheet according to one embodiment of the present invention, in which the anisotropic filler is a fibrous material.
[0011] The thermally conductive sheet 10 of this embodiment contains an anisotropic filler 12 in a polymer matrix 14, and the surfaces 10A and 10B have the anisotropic filler 12 exposed, and the arithmetic mean curvature (Spc) of the peaks is 18,000 (1 / mm) or less.
[0012] According to the above configuration, even when the anisotropic filler 12 is exposed from the thermally conductive sheet surface 10A and the sheet surface 10A is uneven, the arithmetic mean curvature (Spc) of the peaks is 18,000 (1 / mm) or less, so the sheet surface 10A is smooth, the contact area with the heating element is increased, and the thermal resistance value can be reduced. The arithmetic mean curvature (Spc) of the peaks is preferably 17,000 (1 / mm) or less, and more preferably 16,000 (1 / mm) or less. Furthermore, the arithmetic mean curvature (Spc) of the peaks is preferably 1,000 (1 / mm) or more, and more preferably 5,000 (1 / mm) or more.
[0013] The arithmetic mean curvature of the peaks (Spc) is a parameter that represents the arithmetic mean of the principal curvatures of the peaks within a defined area, measured in accordance with ISO 25178. A small value indicates that the point of contact with the heating element is rounded. On the other hand, a large value indicates that the point of contact with the heating element is sharp. Although the location of the rounded contact point is not certain, for example, the end or end face of the anisotropic filler exposed on the surface, or the surface consisting of the end of the anisotropic filler and the surface of the polymer matrix, could be the rounded contact point. The arithmetic mean curve (Spc) of the peaks is calculated based on the measured area (e.g., 1 mm 2 The surface profile of the two-dimensional area can be calculated by measuring it using a commercially available laser microscope.
[0014] To achieve an arithmetic mean curvature (Spc) of 18,000 (1 / mm) or less, the surface may be polished using abrasive paper with a grit size of #120 to #20,000, with the number of polishing cycles appropriately set according to the grit size. Furthermore, the oriented molded article may be adjusted to an E hardness of about 10 to 80 before being made into the thermally conductive sheet 10, and then sliced into sheets and polished as described above.
[0015] As shown in Fig. 1, it is preferable that the anisotropic filler 12 is oriented in the thickness direction of the thermally conductive sheet 10 at least inside the thermally conductive sheet 10. According to the above configuration, the thermally conductive sheet 10 exhibits high thermal conductivity in the thickness direction, has a smooth sheet surface, and has a low thermal resistance value. To orient the anisotropic filler 12, treatments such as magnetic field orientation and flow orientation, which will be described later, may be carried out.
[0016] Here, the state in which the anisotropic fillers 12 are oriented in the thickness direction of the thermally conductive sheet 10 refers to a state in which the major axis directions of more than 60% of the anisotropic fillers 12, by number ratio, are oriented within a range of 20° from the thickness direction of the thermally conductive sheet 10. This state of orientation can be confirmed by observing a cross section of the thermally conductive sheet 10 along the thickness direction with an electron microscope.
[0017] The arithmetic mean height (Sa) of the surface 10A of the thermally conductive sheet 10 is preferably 20 μm or less, and more preferably 1 to 15 μm. When the arithmetic mean height (Sa) is 20 μm or less, the sheet surface is smooth, the contact area with the heating element or the like is increased, and the thermal resistance value can be reduced. The arithmetic mean height (Sa) can be measured using a commercially available surface texture measuring device, and specifically, it can be measured by the method described in the examples.
[0018] To achieve an arithmetic mean height (Sa) of 20 μm or less, the surface can be polished using abrasive paper with a relatively coarse grain size of, for example, #120 to #20000, and the number of polishing cycles can be appropriately set according to the grain size.
[0019] Furthermore, the surface 10A of the thermally conductive sheet 10 preferably has an interface developed area ratio (Sdr) of 70 or less, more preferably 1 to 60. Even if the thermally conductive filler is exposed from the surface 10A of the thermally conductive sheet 10 and the sheet surface is uneven, by having an interface developed area ratio (Sdr) of 70 or less, the sheet surface is smooth, the contact area with the heat-generating element or the like is increased, and the thermal resistance value can be reduced.
[0020] The developed area ratio (Sdr) of the interface is the ratio of the developed area (surface area) of the defined area to the area (for example, 1 mm 2 ), and a completely flat surface has a developed area ratio Sdr of 0. The developed area ratio (Sdr) of the interface can be measured by the method described in the Examples.
[0021] In addition, to achieve an interface developed area ratio (Sdr) of 70 or less, the surface can be polished using a relatively coarse abrasive paper with a grit size of #120 to #20000, for example, and the number of polishing passes can be appropriately set according to the grit size.
[0022] In this embodiment, the thermally conductive sheet 10 further contains a non-anisotropic filler 16. The thermal conductivity of the thermally conductive sheet 10 is further improved by containing the non-anisotropic filler 16. Details of the non-anisotropic filler 16 will be described later.
[0023] The configuration of the thermally conductive sheet according to this embodiment will be described in more detail below. <Polymer matrix> The polymer matrix 14 used in the thermally conductive sheet 10 is a polymer compound such as elastomer or rubber, and is preferably formed by curing a liquid polymer composition (curable polymer composition) consisting of a mixture of a base resin and a curing agent. The curable polymer composition may be, for example, one consisting of uncrosslinked rubber and a crosslinking agent, or one containing a monomer, prepolymer, or the like and a curing agent. The curing reaction may be room temperature curing or heat curing.
[0024] An example of the polymer matrix 14 formed from the curable polymer composition is silicone rubber. In the case of silicone rubber, an addition reaction curable silicone is preferably used as the polymer matrix (curable polymer composition) 14. More specifically, the curable polymer composition may contain an alkenyl group-containing organopolysiloxane and a hydrogenorganopolysiloxane.
[0025] In addition to the above, various synthetic rubbers can be used as rubber, including acrylic rubber, nitrile rubber, isoprene rubber, urethane rubber, ethylene propylene rubber, styrene-butadiene rubber, butadiene rubber, fluororubber, and butyl rubber. When using these rubbers, the synthetic rubbers may be crosslinked or left uncrosslinked (i.e., uncured) in the thermally conductive sheet. Uncrosslinked rubbers are primarily used for flow orientation. Furthermore, when crosslinking (i.e., curing) is performed, as explained above, the polymer matrix may be a cured curable polymer composition comprising an uncrosslinked synthetic rubber and a crosslinking agent. The elastomer may be a thermoplastic elastomer such as a polyester thermoplastic elastomer or a polyurethane thermoplastic elastomer, or a thermosetting elastomer formed by curing a liquid polymer composition containing a base agent and a curing agent, such as a polyurethane elastomer formed by curing a polymer composition containing a hydroxyl group-containing polymer and an isocyanate. Among the above, it is preferable to use silicone rubber, especially addition reaction curable silicone, because the polymer matrix after curing is particularly flexible and has good filling properties for the thermally conductive filler.
[0026] The polymer composition for forming the polymer matrix may be composed of a polymer compound alone, or may be composed of a polymer compound and a plasticizer. Plasticizers are preferably used when synthetic rubber is used, and the inclusion of a plasticizer can increase the flexibility of the polymer matrix when not crosslinked. The content of the polymer matrix, expressed as a volume-based filling rate (volume filling rate), is preferably 20 to 50% by volume, and more preferably 25 to 45% by volume, based on the total volume of the thermally conductive sheet.
[0027] (additives) In the thermally conductive sheet 10, various additives may be further blended into the polymer matrix 14 to the extent that the functionality of the thermally conductive sheet 10 is not impaired. Examples of additives include at least one selected from dispersants, coupling agents, adhesives, flame retardants, antioxidants, colorants, anti-settling agents, etc. Furthermore, when the curable polymer composition is to be crosslinked or cured as described above, a crosslinking accelerator, curing accelerator, etc. that accelerates crosslinking or curing may be blended as an additive.
[0028] <Anisotropic filler> The anisotropic filler 12 blended into the polymer matrix 14 is a filler that has anisotropic shape and is capable of orientation. The anisotropic filler 12 is preferably a thermally conductive filler. The anisotropic filler 12 is preferably a fibrous filler (e.g., a fibrous material such as carbon fiber) or a flaky filler (e.g., a flaky material such as graphite, graphene, or boron nitride). Even if these anisotropic fillers are exposed on the surface of the thermally conductive sheet 10, causing the sheet surface to have small irregularities, the sheet surface still has good smoothness, and the contact area with the heating element, etc. is increased, thereby further reducing the thermal resistance value.
[0029] The anisotropic filler 12 has a high aspect ratio, specifically an aspect ratio of more than 2, and preferably an aspect ratio of 5 or more. By making the aspect ratio greater than 2, it becomes easier to orient the anisotropic filler 12 in the thickness direction, and the thermal conductivity of the thermally conductive sheet 10 becomes easier to increase. The upper limit of the aspect ratio is not particularly limited, but is practically 100. The aspect ratio is the ratio of the length in the long axis direction to the length in the short axis direction of an anisotropic filler, and in the case of fibrous materials, it means the fiber length / fiber diameter, and in the case of scaly materials, it means the length in the long axis direction of the scaly materials / thickness. The anisotropic filler is preferably a fibrous material from the viewpoint of increasing thermal conductivity.
[0030] The content of the anisotropic filler 12 in the thermally conductive sheet is preferably 30 to 500 parts by mass, and more preferably 50 to 300 parts by mass, per 100 parts by mass of the polymer matrix. The content of the anisotropic filler 12, expressed as a volume-based filling rate (volume filling rate), is preferably 5 to 60% by volume, and more preferably 8 to 45% by volume, of the total amount of the thermally conductive sheet. By making the content of the anisotropic filler 12 30 parts by mass or more, it becomes easier to increase thermal conductivity, and by making it 300 parts by mass or less, it becomes easier to make the viscosity of the mixed composition described below appropriate, and the orientation of the anisotropic filler 12 becomes good.
[0031] When the anisotropic filler 12 is a fibrous material, the average fiber length is preferably 50 to 500 μm, and more preferably 70 to 350 μm. When the average fiber length is 50 μm or more, the anisotropic filler 12 is in proper contact with each other within the thermally conductive sheet 10, ensuring a heat transfer path. On the other hand, if the average fiber length is 500 μm or less, the bulk of the anisotropic filler 12 becomes low, and it becomes possible to highly fill the polymer matrix.
[0032] Furthermore, the average fiber length of the fiber material is preferably shorter than the thickness of the thermally conductive sheet 10. Having the average fiber length shorter than the thickness prevents the fiber material from protruding more than necessary from the surface of the thermally conductive sheet 10. Furthermore, when the anisotropic filler 12 is a scaly material, its average particle size is preferably 10 to 400 μm, more preferably 15 to 200 μm, and particularly preferably 15 to 130 μm. By setting the average particle size to 10 μm or more, the anisotropic filler 12 particles in the thermally conductive sheet can easily come into contact with each other, ensuring a heat transfer path. On the other hand, by setting the average particle size to 400 μm or less, the bulk of the thermally conductive sheet 10 is reduced, allowing the polymer matrix 14 to be highly filled with the anisotropic filler 12. The average fiber length of the carbon fibers and the average particle size of the scaly material can be calculated from, for example, the fiber length and major axis by observing the anisotropic filler under a microscope. More specifically, the fiber lengths and major axes of 50 random anisotropic fillers can be measured using, for example, an electron microscope or an optical microscope, and the average values (arithmetic mean values) can be used as the average fiber length and average particle size.
[0033] The anisotropic filler 12 may be made of a known material having thermal conductivity, but it is preferable that the filler has diamagnetic properties so that it can be magnetically oriented as described below. Specific examples of the anisotropic filler 12 include carbon-based materials such as carbon fiber or scaly carbon powder, metal materials such as metal fiber, metal oxides, boron nitride, metal nitrides, metal carbides, and metal hydroxides. Among these, carbon-based materials are preferred because they have a low specific gravity and good dispersibility in the polymer matrix 14, and graphitized carbon materials with high thermal conductivity are more preferred. Graphitized carbon materials have diamagnetic properties due to the alignment of graphite planes in a specific direction. Boron nitride and other materials also have diamagnetic properties due to the alignment of crystal planes in a specific direction.
[0034] Furthermore, although not particularly limited, the thermal conductivity of the anisotropic filler 12 along the anisotropic direction (i.e., the long axis direction) is generally 60 W / m·K or more, and preferably 400 W / m·K or more. The upper limit of the thermal conductivity of the anisotropic filler 12 is not particularly limited, but is, for example, 2000 W / m·K or less. The thermal conductivity can be measured by the laser flash method or a method in accordance with ASTM D5470.
[0035] The anisotropic filler 12 may be used alone or in combination of two or more types. For example, anisotropic fillers 12 having at least two different average particle sizes or average fiber lengths may be used as the anisotropic filler 12. When anisotropic fillers 12 of different sizes are used, smaller anisotropic fillers 12 are embedded between the relatively larger anisotropic fillers 12, which is thought to enable the anisotropic fillers 12 to be densely packed in the polymer matrix and to improve heat conduction efficiency.
[0036] Graphitized carbon fiber is preferred as the carbon fiber used as the anisotropic filler 12. Also, flake graphite powder is preferred as the scaly carbon powder. Of these, graphitized carbon fiber is more preferred as the anisotropic filler. Graphitized carbon fiber has graphite crystal planes that are aligned in the fiber axis direction, providing high thermal conductivity in the fiber axis direction. Therefore, by aligning the fiber axis direction in a predetermined direction, it is possible to increase thermal conductivity in a specific direction. Furthermore, flake graphite powder has graphite crystal planes that are aligned in the in-plane direction of the flake surfaces, providing high thermal conductivity in the in-plane direction. Therefore, by aligning the flake surfaces in a predetermined direction, it is possible to increase thermal conductivity in a specific direction. Graphitized carbon fiber and flake graphite powder with a high degree of graphitization are preferred.
[0037] The graphitized carbon materials, such as the graphitized carbon fiber and flake graphite powder, can be obtained by graphitizing the following raw materials. Examples include condensed polycyclic hydrocarbon compounds such as naphthalene, condensed heterocyclic compounds such as PAN (polyacrylonitrile), and pitch. However, it is particularly preferable to use graphitized mesophase pitch, polyimide, or polybenzazole, which have a high degree of graphitization. For example, by using mesophase pitch, the pitch is anisotropically oriented in the fiber axis direction in the spinning process described below, thereby obtaining graphitized carbon fibers with excellent thermal conductivity in the fiber axis direction.
[0038] Graphitized carbon fibers can be obtained by sequentially subjecting a raw material to spinning, infusibilization, and carbonization treatments, pulverizing or cutting to a predetermined particle size, and then graphitizing the fibers, or by carbonizing, pulverizing, or cutting, and then graphitizing the fibers. When pulverizing or cutting is performed before graphitization, condensation polymerization reactions and cyclization reactions are more likely to proceed on the newly exposed surface during the graphitization treatment, thereby increasing the degree of graphitization and enabling the production of graphitized carbon fibers with even improved thermal conductivity. On the other hand, when spun carbon fibers are pulverized after graphitization, the carbon fibers after graphitization are stiff and therefore easy to pulverize, and carbon fiber powder with a relatively narrow fiber length distribution can be obtained by pulverizing for a short period of time.
[0039] <Non-anisotropic filler> The non-anisotropic filler 16 is a thermally conductive filler contained in the thermally conductive sheet 10 separately from the anisotropic filler 12, and together with the anisotropic filler 12, it is a material that imparts thermal conductivity to the thermally conductive sheet 10. In this embodiment, by filling the thermally conductive sheet 10 with the non-anisotropic filler 16, an increase in viscosity is suppressed and dispersibility is improved prior to the sheet hardening stage. Furthermore, when anisotropic fillers 12 are mixed together, it is difficult to increase the contact area between the fillers, for example, if the fiber length is large. However, by filling the gaps with the non-anisotropic filler 16, a heat transfer path can be formed, resulting in a thermally conductive sheet 10 with high thermal conductivity. The non-anisotropic filler 16 is a filler that has substantially no anisotropy in shape, and is a filler that does not orient in a predetermined direction even in an environment in which the anisotropic filler 12 orients in that predetermined direction, such as under the generation of magnetic lines of force or under the action of shear force, as described below.
[0040] The aspect ratio of the non-anisotropic filler 16 is 2 or less, and preferably 1.5 or less. In this embodiment, by including a non-anisotropic filler with such a low aspect ratio, a thermally conductive filler is appropriately interposed in the gaps between the anisotropic fillers 12, resulting in a thermally conductive sheet 10 with high thermal conductivity. Furthermore, by setting the aspect ratio to 2 or less, an increase in the viscosity of the mixed composition described below can be prevented, enabling high filling.
[0041] Specific examples of the non-anisotropic filler 16 include metals, metal oxides, metal nitrides, metal hydroxides, carbon materials, oxides, nitrides, carbides, etc. The shape of the non-anisotropic filler may be spherical, irregular powder, etc. In the non-anisotropic filler 16, examples of metals include aluminum, copper, and nickel; examples of metal oxides include aluminum oxide (alumina), magnesium oxide, and zinc oxide; and examples of metal nitrides include aluminum nitride. Examples of metal hydroxides include aluminum hydroxide. Furthermore, examples of carbon materials include spherical graphite. Examples of oxides, nitrides, and carbides other than metals include quartz, boron nitride, and silicon carbide. Of the above, the non-anisotropic filler 16 is preferably selected from alumina, aluminum, zinc oxide, boron nitride, and aluminum nitride, and aluminum and alumina are particularly preferred from the viewpoints of packing properties and thermal conductivity, with alumina being more preferred. The non-anisotropic filler 16 may be one of the above materials, or two or more of them may be used in combination.
[0042] The average particle size of the non-anisotropic filler 16 is preferably 0.1 to 50 μm, more preferably 0.5 to 35 μm, and particularly preferably 1 to 15 μm. By setting the average particle size to 50 μm or less, problems such as disturbance of the orientation of the anisotropic filler 12 are less likely to occur. Furthermore, by setting the average particle size to 0.1 μm or more, the specific surface area of the non-anisotropic filler 16 does not become larger than necessary, and even if a large amount is blended, the viscosity of the mixed composition is less likely to increase, making it easier to pack the non-anisotropic filler 16 at a high density. The non-anisotropic filler 16 may be, for example, a non-anisotropic filler 16 having at least two different average particle sizes. The average particle size of the non-anisotropic filler 16 can be measured by observation using an electron microscope or the like. More specifically, the particle sizes of 50 random non-anisotropic fillers can be measured using, for example, an electron microscope or an optical microscope, and the average (arithmetic mean) of the particle sizes can be used as the average particle size. Alternatively, the average particle size is the volume average particle size of the particle size distribution measured by a laser diffraction scattering method (JIS R1629).
[0043] The content of the non-anisotropic filler 16 is preferably in the range of 200 to 800 parts by mass, and more preferably in the range of 300 to 700 parts by mass, relative to 100 parts by mass of the polymer matrix. The content of the non-anisotropic filler 16, expressed as a volume-based filling rate (volume filling rate), is preferably 30 to 60% by volume, and more preferably 40 to 55% by volume, relative to the total amount of the thermally conductive sheet. By setting the non-anisotropic filler content at 200 parts by mass or more, the amount of non-anisotropic filler 16 present in the gaps between the anisotropic fillers 12 is sufficient, resulting in good thermal conductivity. On the other hand, by setting the content at 800 parts by mass or less, the effect of increasing thermal conductivity according to the content can be obtained, and the non-anisotropic filler 16 does not inhibit the thermal conduction of the anisotropic filler 12. Furthermore, by setting the content within the range of 300 to 700 parts by mass, the thermal conductivity of the thermally conductive sheet 10 is excellent, and the viscosity of the mixed composition is also suitable.
[0044] The ratio of the volume filling rate of the non-anisotropic filler 16 to the volume filling rate of the anisotropic filler is preferably 2 to 5, and more preferably 2 to 3. By setting the volume filling rate ratio within the above range, the non-anisotropic filler 16 is appropriately filled between the anisotropic fillers, forming efficient heat transfer paths, thereby improving the thermal conductivity of the thermally conductive sheet 10.
[0045] <Thermal conductive sheet> The thermal resistance value of the thermally conductive sheet 10 in the thickness direction of the sheet is preferably less than 1°C / W, more preferably 0.5°C / W or less, and even more preferably 0.2°C / W or less. By keeping the thermal resistance value at a certain value or less, the thermally conductive sheet 10 can easily transfer heat from a heat generating body to a heat dissipating body. The smaller the thermal resistance value, the better, but it is usually 0.01°C / W or more. The thermal resistance value can be measured by the method described in the examples.
[0046] The thermal conductivity of the thermally conductive sheet 10 in the thickness direction is, for example, 5 W / m·K or more, preferably 10 W / m·K or more, more preferably 15 W / m·K or more, and even more preferably 18 W / m·K or more. By setting the thermal conductivity at or above these lower limits, the thermal conductivity of the thermally conductive sheet 10 in the thickness direction can be made excellent. There is no particular upper limit, but the thermal conductivity of the thermally conductive sheet 10 in the thickness direction is, for example, 50 W / m·K or less. The thermal conductivity is measured according to a method in accordance with ASTM D5470-06.
[0047] As described above, the anisotropic filler 12 is exposed on the surface of the thermally conductive sheet 10, making the surface a non-adhesive surface. The non-adhesive surface is not easily sticky when touched by a worker's hand, and is easily peeled off when applied with pressure to contact objects such as heat generating elements and heat dissipating elements, which will be described later. Furthermore, the non-adhesive surface of the thermally conductive sheet 10 allows it to slide when assembled to electronic devices and the like.
[0048] The thickness of the thermally conductive sheet 10 is considered to be in the range of 0.1 to 5.0 mm, but is not necessarily limited to this thickness range. The thickness can be changed as appropriate depending on the shape and application of the electronic device in which the thermally conductive sheet 10 is installed, but a more preferable thickness is 0.1 to 0.3 mm. A thickness of 0.1 to 0.3 mm makes the thermally conductive sheet a thin film that easily conducts heat.
[0049] The thermally conductive sheet 10 is used inside electronic devices, etc. Specifically, the thermally conductive sheet is interposed between a heat generating element and a heat dissipating element, and transfers heat generated by the heat generating element to the heat dissipating element by thermal conduction, where the heat is dissipated from the heat dissipating element. Here, examples of the heat generating element include various electronic components used inside the electronic device, such as a CPU, a power amplifier, and a power source such as a battery. Examples of the heat dissipating element include a heat sink, a heat pipe, a heat pump, and the metal housing of the electronic device. The thermally conductive sheet is used by being pressed against the heat generating element and the heat dissipating element on both surfaces, respectively.
[0050] <Method for manufacturing thermally conductive sheets> The thermally conductive sheet of this embodiment can be produced by, but is not particularly limited to, a method including the following steps (A), (B), and (C), for example. Step (A): A step of obtaining an oriented molded body in which the anisotropic filler is oriented along one direction that is the thickness direction of the thermal conductive sheet. Step (B): A step of cutting the oriented molded body into a sheet to obtain a sheet-like molded body. Step (C): A step of polishing the surface of the sheet-shaped molded body Each step will be described in more detail below.
[0051] [Process (A)] In step (A), an oriented molded body is formed from a mixed composition containing, for example, an anisotropic filler, a non-anisotropic filler, and a polymer composition serving as a raw material for the polymer matrix. The mixed composition is preferably cured to form an oriented molded body. More specifically, the oriented molded body can be obtained by a magnetic field orientation method or a flow orientation method, with the magnetic field orientation method being preferred.
[0052] (Magnetic field orientation method) In the magnetic field orientation method, a mixed composition containing a liquid polymer composition that becomes a polymer matrix after curing, an anisotropic filler, and a non-anisotropic filler is poured into a mold or the like and placed in a magnetic field to orient the anisotropic filler along the magnetic field, and then the polymer composition is cured to obtain an oriented molded product. The oriented molded product is preferably in the shape of a block. A release film may be placed inside the mold at a portion that comes into contact with the mixed composition. For example, a resin film with good releasability or a resin film whose one side has been treated with a release agent or the like is used as the release film. The use of the release film makes it easier for the oriented molded article to be released from the mold.
[0053] The viscosity of the mixed composition used in the magnetic field orientation method is preferably 10 to 300 Pa·s in order to achieve magnetic field orientation. A viscosity of 10 Pa·s or higher makes it difficult for anisotropic and non-anisotropic fillers to settle. A viscosity of 300 Pa·s or lower improves fluidity, allowing the anisotropic filler to be properly oriented in the magnetic field, and preventing problems such as excessively long orientation times. The viscosity is measured at 25°C using a rotational viscometer (Brookfield viscometer DV-E, spindle SC4-14) at a rotational speed of 10 rpm. However, when anisotropic or non-anisotropic fillers that are difficult to settle are used, or when additives such as anti-settling agents are combined, the viscosity of the mixed composition may be less than 10 Pa·s.
[0054] In the magnetic field orientation method, magnetic field generating sources for applying magnetic field lines include superconducting magnets, permanent magnets, electromagnets, etc., but superconducting magnets are preferred because they can generate a magnetic field with a high magnetic flux density. The magnetic flux density of the magnetic field generated by these magnetic field generating sources is preferably 1 to 30 Tesla. If the magnetic flux density is 1 Tesla or higher, it becomes possible to easily orient the above-mentioned anisotropic filler made of a carbon material, etc. Furthermore, if the magnetic flux density is 30 Tesla or lower, practical production becomes possible. The polymer composition may be cured by heating, for example, at a temperature of about 50 to 150° C. The heating time is, for example, about 10 minutes to 3 hours.
[0055] (flow orientation method) In the flow orientation method, a shear force is applied to the mixed composition to produce a preliminary sheet in which the anisotropic filler is oriented in the plane direction, and multiple sheets of this are stacked to produce a laminated block, which is then used as an oriented molded body. More specifically, in the flow orientation method, an anisotropic filler, a non-anisotropic filler, and various additives, if necessary, are first mixed into a polymer composition and stirred to prepare a mixed composition in which the mixed solids are uniformly dispersed. Here, the polymer compound used in the polymer composition may be one that is liquid at room temperature (23°C) or one that is solid at room temperature. The polymer composition may also contain a plasticizer. The mixed composition has a relatively high viscosity so that a shear force is applied when the mixed composition is stretched into a sheet, and specifically, the viscosity of the mixed composition is preferably 3 to 50 Pa s. In order to achieve the above viscosity, the mixed composition is preferably blended with a solvent.
[0056] Next, the mixed composition is flattened and stretched while applying shear force to form a sheet (preliminary sheet). By applying shear force, the anisotropic filler can be oriented in the shear direction. As a means for forming the sheet, for example, the mixed composition can be applied to a substrate film using a coating applicator such as a bar coater or a doctor blade, or by extrusion molding or discharge from a nozzle, and then, if necessary, dried or semi-cured. The thickness of the preliminary sheet is preferably about 50 to 250 μm. In the preliminary sheet, the anisotropic filler is oriented in one direction along the surface direction of the sheet. Next, multiple preliminary sheets are stacked on top of each other so that they have the same orientation direction, and the mixed composition is cured as needed by heating, ultraviolet irradiation, etc., while the preliminary sheets are adhered to each other by hot pressing, etc. to form a laminated block, which can be used as an oriented molded body.
[0057] [Process (B)] In step (B), the oriented molded product obtained in step (A) is cut perpendicular to the orientation direction of the anisotropic filler by slicing or the like to obtain a sheet-like molded product. Slicing can be performed, for example, using a shear blade or a laser. By slicing or cutting the sheet-like molded product, the tips of the anisotropic filler are exposed from the polymer matrix on each surface, which is the cut surface. Furthermore, at least a portion of the exposed anisotropic filler protrudes from each surface. Most of the exposed anisotropic filler is oriented in the thickness direction without collapsing.
[0058] Here, the oriented molded body preferably has a Type E hardness, as defined by JIS K6253, of 10 to 80, more preferably 20 to 70. When the Type E hardness is 10 to 80, when slicing the sheet-shaped molded body, the polymer matrix is more likely to be cut than the anisotropic filler, making it easier to expose the anisotropic filler. Furthermore, after slicing to form a thermally conductive sheet, polishing the surface can also expose the anisotropic filler, since the polymer matrix is more easily worn than the anisotropic filler. Furthermore, if the anisotropic filler is worn in an exposed state, the edges of the exposed anisotropic filler are crushed, easily forming edges that bulge toward the surface of the thermally conductive sheet. These edges increase the contact area with the adherend, thereby further improving thermal conductivity.
[0059] [Process (C)] In step (C), the surface of the sheet-like molded body on which the anisotropic filler is exposed is polished. The surface may be polished using, for example, abrasive paper, abrasive film, abrasive cloth, abrasive belt, etc. In this manufacturing method, by polishing the surface of the sheet-like molded body, the anisotropic filler is exposed and the arithmetic mean curvature (Spc) of the peaks is set to 18,000 (1 / mm) or less. Therefore, for example, the properties of the abrasive paper include abrasive grains with an average grain size (D50) of 0.1 to 100 μm, preferably 9 to 60 μm. Using abrasive paper with an average grain size of 0.1 μm or more allows the anisotropic filler to be exposed from the sheet surface while smoothing the arithmetic mean peak curvature (Spc) to a predetermined value or less. Specifically, it is possible to round and smooth the contact point with the contact surface of a heating element, etc. Furthermore, using abrasive paper with an average grain size of 100 μm or less prevents practically problematic scratches on the surface of the thermally conductive sheet. For the same reasons as above, the grain size of the abrasive grains in the abrasive paper is preferably #120 to 20,000, more preferably #300 to 15,000, and more preferably #320 to 4,000. The polishing method can be, for example, polishing by continuously contacting the surface of the thermal conductive sheet with abrasive paper in the same linear direction, polishing by moving the paper back and forth over a certain distance, polishing by rotating the paper in the same direction, or polishing by contacting the paper in various directions. The degree of polishing can be determined, for example, while observing the surface condition, and in the case of reciprocating polishing, 1 to 300 reciprocating strokes is preferred, 2 to 200 strokes is more preferred, and 3 to 50 strokes is even more preferred. Specifically, polishing is preferably performed to the extent that the protruding length of the anisotropic filler is 100 μm or less, and even more preferably to the extent that the protruding length is 50 μm or less.
[0060] In the above description, the anisotropic filler 12 is exposed on both surfaces 10A, 10B of the thermally conductive sheet 10, and the arithmetic mean peak curvature (Spc) is 18,000 (1 / mm) or less while the anisotropic filler 12 is exposed on both surfaces 10A, 10B. However, in the present invention, the thermally conductive sheet may have the anisotropic filler 12 exposed on only one of the surfaces 10A, 10B. Therefore, the other of surfaces 10A, 10B may have an arithmetic mean curvature (Spc) of 18000 (1 / mm) or less while anisotropic filler 12 is exposed, or may have an arithmetic mean curvature (Spc) of 18000 (1 / mm) or more even when anisotropic filler 12 is exposed. In this case, polishing in step (C) is performed on only one of the surfaces, and the other surface is not polished, or if polishing is performed, it is preferable to polish it under conditions other than those specified in step (C). Furthermore, polished materials are very flat even before they are used by being in close contact with a heating element, a heat sink, etc. and compressed, and the surface condition after compression remains almost unchanged, only slightly flattened from before compression. In contrast, unpolished materials can be significantly flattened by compression, but cannot be flattened to the same degree as polished materials.
[0061] Alternatively, the other of the two surfaces 10A and 10B may be a surface in which the anisotropic filler 12 is embedded within the polymer matrix 12. The oriented molded body produced by the magnetic field orientation method described above has an outermost surface that is a skin layer containing a lower anisotropic filler than other portions, typically containing no anisotropic filler. Therefore, for example, by using the other of the two surfaces 10A and 10B of the thermally conductive sheet 10 as the outermost surface of the oriented molded body, the other of the two surfaces 10A and 10B can be a surface in which the anisotropic filler 12 is embedded within the polymer matrix 12. The surface in which the anisotropic filler 12 is embedded within the polymer matrix 12 becomes an adhesive surface. The adhesive surface can be attached to a contact object, such as a heat sink or heat generator, thereby fixing the contact object.
[0062] [Second embodiment] Next, a thermally conductive sheet according to a second embodiment of the present invention will be described with reference to FIG. In the first embodiment, the thermally conductive sheet 10 contains a non-anisotropic filler 16 in addition to the anisotropic filler 12 as fillers, but the thermally conductive sheet 20 of this embodiment does not contain the non-anisotropic filler 16, as shown in Fig. 2. That is, in the thermally conductive sheet of the second embodiment, for example, only carbon fiber may be used as the filler. The other configurations of the thermally conductive sheet 20 of the second embodiment are the same as those of the thermally conductive sheet 10 of the first embodiment described above, except that no non-anisotropic filler is contained, and therefore a description thereof will be omitted.
[0063] In this embodiment, as in the first embodiment, the anisotropic filler 12 is exposed on at least one of the surfaces 20A, 20B of the thermally conductive sheet 20, and the same effects as in the first embodiment can be obtained.
[0064] In this embodiment, as in the first embodiment, the anisotropic filler 12 is exposed on at least one surface, and the arithmetic mean curvature (Spc) of the peaks is 18,000 (1 / mm) or less, thereby improving the thermal conductivity in the thickness direction. [Example]
[0065] The present invention will be explained in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0066] In this example, the physical properties of the thermally conductive sheet were evaluated by the following methods. [Arithmetic mean curvature of the peak (Spc), arithmetic mean height (Sa), and developed area ratio of the interface (Sdr)] Surface quality analysis was performed using a laser microscope (Keyence Corporation, VK-X150) in accordance with ISO 25178. Specifically, the surface profile of a two-dimensional area of 1000 μm × 1000 μm was measured using a laser method at a lens magnification of 10x. The average value of measurements taken at three locations on the same sample was used as the arithmetic mean curve (Spc) of the peaks. The arithmetic mean height (Sa) and the developed area ratio of the interface (Sdr) were also measured at three locations on the same sample, and the average values were used as the arithmetic mean height (Sa) and the developed area ratio of the interface (Sdr), respectively.
[0067] [Thermal resistance value] The thermal resistance value was measured using a thermal resistance measuring device as shown in FIG. 3 by the method described below. Specifically, for each sample, a test piece S measuring 30 mm × 30 mm was prepared for this test. Each test piece S was then attached to a copper block 22 with a measurement surface of 25.4 mm × 25.4 mm and sides covered with a heat insulating material 21, and sandwiched between upper copper blocks 23. A load was applied by a load cell 26, and the thickness was set to 90% of the original thickness. Here, the lower copper block 22 was in contact with a heater 24. The upper copper block 23 was also covered with a heat insulating material 21 and connected to a heat sink 25 equipped with a fan. Next, the heater 24 was made to generate heat at a heat output of 25 W, and after 10 minutes when the temperature reached a substantially steady state, the temperature (θ j0 ), the temperature of the lower copper block 22 (θ j1 ) and the heat generation amount (Q) of the heater were measured, and the thermal resistance value of each sample was calculated using the following formula (1). Thermal resistance=(θ j1 -θ j0 ) / Q... Equation (1) In equation (1), θ j1 is the temperature of the lower copper block 22, θ j0 is the temperature of the upper copper block 23, and Q is the amount of heat generated.
[0068] [Type E hardness as specified in JIS K6253] Type E hardness was measured based on Japanese Industrial Standard JIS K 6253. Specifically, the oriented molded article produced in each example was measured using a Type E durometer.
[0069] [Orientation rate] The cross section of the produced thermal conductive sheet was observed under an electron microscope, 100 anisotropic fillers (carbon fibers) were extracted, and the number of anisotropic fillers oriented in the thickness direction of the sheet was calculated. Those with 61 or more (61%) oriented were marked with a good mark, and those with less than 60 (60%) oriented were marked with an unsatisfactory mark. Carbon fibers whose major axis direction was within a range of 20° from the thickness direction of the thermally conductive sheet were determined to be oriented.
[0070] [Example 1] A mixed composition was obtained by mixing an alkenyl group-containing organopolysiloxane and a hydrogenorganopolysiloxane (total 100 parts by mass, volume filling rate 36% by volume) as a polymer matrix (polymer composition), 150 parts by mass (volume filling rate 30% by volume) of carbon fiber (graphitized carbon fiber with an average fiber length of 100 μm, an aspect ratio of 10, and a thermal conductivity of 500 W / m·K) as an anisotropic filler, and 200 parts by mass (volume filling rate 18% by volume) of alumina powder (spherical, average particle size 3 μm, aspect ratio 1.0) and 100 parts by mass (volume filling rate 13% by volume) of aluminum powder (irregular shape, average particle size 3 μm) as non-anisotropic fillers. Next, the mixed composition was poured into a mold set to a thickness sufficiently greater than that of the thermally conductive sheet, and an 8 T magnetic field was applied in the thickness direction to orient the carbon fibers in the thickness direction. The matrix was then hardened by heating at 80°C for 60 minutes, yielding a block-shaped oriented molded body. Next, the block-shaped oriented molded product was sliced into sheets with a thickness of 1 mm using a shear blade, thereby obtaining sheet-shaped molded products with exposed carbon fibers.
[0071] Subsequently, both surfaces of the sheet-like molded body were reciprocally polished 50 times with coarse abrasive paper A (grain size #320) with an average abrasive grain size (D50) of 60 μm to obtain a thermally conductive sheet.
[0072] [Example 2] A thermally conductive sheet was obtained in the same manner as in Example 1, except that the abrasive paper A was changed to abrasive paper B (grain size #4000) with finer abrasive grains and an average grain size (D50) of 3 μm, and the number of times of abrasion was changed to 15 back and forth strokes.
[0073] [Example 3] A thermally conductive sheet was obtained in the same manner as in Example 1, except that the abrasive paper A was changed to abrasive paper C (grain size #15000) with even finer abrasive grains and an average grain size (D50) of 0.3 μm, and the number of times of abrasion was changed to three back and forth passes.
[0074] [Example 4] A thermally conductive sheet was obtained in the same manner as in Example 1, except that the polishing was changed from 50 times back and forth with abrasive paper A to 30 times back and forth with abrasive paper A, followed by 10 times back and forth with abrasive paper B, and then 10 times back and forth with abrasive paper C.
[0075] [Comparative Example 1] A thermally conductive sheet was obtained in the same manner as in Example 1, except that the sheet-like molded body was not polished.
[0076] [Example 5] A mixed composition was obtained by mixing an alkenyl group-containing organopolysiloxane and a hydrogenorganopolysiloxane (total 100 parts by mass, volume filling rate 32% by volume) as a polymer matrix (polymer composition), 150 parts by mass (volume filling rate 26% by volume) of carbon fiber (graphitized carbon fiber with an average fiber length of 100 μm, an aspect ratio of 10, and a thermal conductivity of 500 W / m·K) as an anisotropic filler, and 475 parts by mass (volume filling rate 41% by volume) of alumina powder (spherical, average particle size 3 μm, aspect ratio 1.0) as a non-anisotropic filler. Next, the mixed composition was poured into a mold set to a thickness sufficiently greater than that of the thermally conductive sheet, and an 8 T magnetic field was applied in the thickness direction to orient the carbon fibers in the thickness direction. The matrix was then hardened by heating at 80°C for 60 minutes, yielding a block-shaped oriented molded body. Next, the block-shaped oriented molded product was sliced into sheets with a thickness of 1 mm using a shear blade, thereby obtaining sheet-shaped molded products with exposed carbon fibers.
[0077] Subsequently, both surfaces of the sheet-like molded body were polished back and forth 30 times with abrasive paper A having coarse abrasive grains to obtain a thermally conductive sheet.
[0078] [Example 6] A thermally conductive sheet was obtained in the same manner as in Example 5, except that the abrasive paper A was changed to abrasive paper B with finer abrasive grains and the number of times of abrasion was changed to 15 back and forth. [Example 7] A thermally conductive sheet was obtained in the same manner as in Example 5, except that the abrasive paper A was changed to abrasive paper C with finer abrasive grains and the number of times of abrasion was changed to five times.
[0079] [Example 8] A thermally conductive sheet was obtained in the same manner as in Example 5, except that the 50 back-and-forth polishing with abrasive paper A was changed to 30 back-and-forth polishing with abrasive paper A, followed by 10 back-and-forth polishing with abrasive paper B, and then 10 back-and-forth polishing with abrasive paper C.
[0080] Comparative Example 2 A thermally conductive sheet was obtained in the same manner as in Example 5, except that the sheet-like molded body was not polished.
[0081] The sheet-like molded article or thermally conductive sheet produced in each example was subjected to the above-described measurements and evaluations, and the results are shown in Table 1 below.
[0082] [Table 1]
[0083] [Example 9] A mixed composition was obtained by mixing an alkenyl group-containing organopolysiloxane and a hydrogenorganopolysiloxane (total 100 parts by mass, volume filling rate 36% by volume) as a polymer matrix (polymer composition), 140 parts by mass (volume filling rate 28% by volume) of carbon fiber (graphitized carbon fiber with an average fiber length of 100 μm, an aspect ratio of 10, and a thermal conductivity of 500 W / m·K) as anisotropic fillers, 5 parts by mass (volume filling rate 1% by volume) of graphite (flake graphite powder with an average particle size of 130 μm, an aspect ratio of 10, and a thermal conductivity of 550 W / m·K), and 250 parts by mass (volume filling rate 34% by volume) of aluminum powder (irregular shape, average particle size 3 μm) as a non-anisotropic filler. Next, the mixed composition was poured into a mold set to a thickness sufficiently greater than that of the thermally conductive sheet, and an 8 T magnetic field was applied in the thickness direction to orient the carbon fibers in the thickness direction. The matrix was then hardened by heating at 80°C for 60 minutes, yielding a block-shaped oriented molded body. Next, the block-shaped oriented molded product was sliced into sheets with a thickness of 1 mm using a shear blade, thereby obtaining sheet-shaped molded products with exposed carbon fibers.
[0084] Subsequently, both surfaces of the sheet-like molded body were reciprocally polished 50 times with coarse abrasive paper A (grain size #320) with an average abrasive grain size (D50) of 60 μm to obtain a thermally conductive sheet.
[0085] [Example 10] A thermally conductive sheet was obtained in the same manner as in Example 9, except that the abrasive paper A was changed to abrasive paper B (grain size #4000) with finer abrasive grains and an average grain size (D50) of 3 μm, and the number of abrasive strokes was changed to 15 back and forth strokes.
[0086] [Example 11] A thermally conductive sheet was obtained in the same manner as in Example 9, except that the abrasive paper A was changed to abrasive paper C (grain size #15000) with even finer abrasive grains and an average grain size (D50) of 0.3 μm, and the number of times of abrasion was changed to three back and forth passes.
[0087] [Example 12] A thermally conductive sheet was obtained in the same manner as in Example 9, except that the 50 back-and-forth polishing cycles with abrasive paper A were changed to 30 back-and-forth polishing cycles with abrasive paper A, followed by 10 back-and-forth polishing cycles with abrasive paper B, and then 10 back-and-forth polishing cycles with abrasive paper C.
[0088] Comparative Example 3 A thermally conductive sheet was obtained in the same manner as in Example 9, except that the sheet-like molded body was not polished.
[0089] [Example 13] A mixed composition was obtained by mixing an alkenyl group-containing organopolysiloxane and a hydrogenorganopolysiloxane (total 100 parts by mass, volume filling rate 36% by volume) as a polymer matrix (polymer composition), 150 parts by mass (volume filling rate 30% by volume) of carbon fiber (graphitized carbon fiber with an average fiber length of 100 μm, an aspect ratio of 10, and a thermal conductivity of 500 W / m·K) as an anisotropic filler, and 250 parts by mass (volume filling rate 33% by volume) of aluminum powder (irregular shape, average particle size 3 μm) as a non-anisotropic filler. Next, the mixed composition was poured into a mold set to a thickness sufficiently greater than that of the thermally conductive sheet, and an 8 T magnetic field was applied in the thickness direction to orient the carbon fibers in the thickness direction. The matrix was then hardened by heating at 80°C for 60 minutes, yielding a block-shaped oriented molded body. Next, the block-shaped oriented molded product was sliced into sheets with a thickness of 1 mm using a shear blade, thereby obtaining sheet-shaped molded products with exposed carbon fibers.
[0090] Subsequently, both surfaces of the sheet-like molded body were polished back and forth 30 times with abrasive paper A having coarse abrasive grains to obtain a thermally conductive sheet.
[0091] [Example 14] A thermally conductive sheet was obtained in the same manner as in Example 13, except that the abrasive paper A was changed to abrasive paper B with finer abrasive grains and the number of times of abrasion was changed to 15 back and forth. [Example 15] A thermally conductive sheet was obtained in the same manner as in Example 13, except that the abrasive paper A was changed to abrasive paper C with finer abrasive grains and the number of times of abrasion was changed to five times.
[0092] [Example 16] A thermally conductive sheet was obtained in the same manner as in Example 13, except that the 50 back-and-forth polishing cycles with abrasive paper A were changed to 30 back-and-forth polishing cycles with abrasive paper A, followed by 10 back-and-forth polishing cycles with abrasive paper B, and then 10 back-and-forth polishing cycles with abrasive paper C.
[0093] Comparative Example 4 A thermally conductive sheet was obtained in the same manner as in Example 13, except that the sheet-like molded body was not polished.
[0094] The sheet-like molded article or thermally conductive sheet produced in each example was subjected to the above-described measurements and evaluations, and the results are shown in Table 2 below.
[0095] [Table 2]
[0096] As is clear from the results of the above examples, in the thermally conductive sheet, by exposing the anisotropic filler and having an arithmetic mean curve (Spc) of the peaks of 18,000 (1 / mm) or less, the desired thermal resistance value and thermal conductivity could be obtained, and the thermal conductivity in the thickness direction could be improved. On the other hand, in the comparative example, the desired thermal resistance value and thermal conductivity could not be obtained, and the thermal conductivity in the thickness direction could not be sufficiently improved. [Explanation of symbols]
[0097] 10, 20 Thermally conductive sheet 12 Anisotropic Filler 14 Polymer matrix 21. Insulation 22 Lower Copper Block 23 Upper Copper Block 24 Heater 25 Heatsink 26 load cells S test piece θ j0 Temperature of the upper copper block θ j1 Temperature of the lower copper block
Claims
1. A thermally conductive sheet for use by being disposed between a heat generating body and a heat dissipating body of an electronic device, A thermally conductive sheet containing an anisotropic filler in a polymer matrix. A thermally conductive sheet, at least one of whose surfaces has the anisotropic filler exposed and has an arithmetic mean peak curvature (Spc) of 16238 (1 / mm) or less.
2. 2. The thermally conductive sheet according to claim 1, wherein the anisotropic filler is oriented in the thickness direction of the thermally conductive sheet.
3. The thermally conductive sheet according to claim 1 or 2, wherein the at least one surface has an arithmetic mean height (Sa) of 20 μm or less.
4. The thermally conductive sheet according to any one of claims 1 to 3, wherein the surface of the thermally conductive sheet has an interface developed area ratio (Sdr) of 70 or less.
5. The thermally conductive sheet according to any one of claims 1 to 4, wherein the anisotropic thermally conductive filler is at least one of a fibrous filler and a scaly filler.
6. The thermally conductive sheet according to any one of claims 1 to 5, having a thickness of 0.1 to 5.0 mm.
7. The thermally conductive sheet according to claim 6, which has a thickness of 0.1 to 0.3 mm.
